Comparative Age-Related Studies on Lingual Histochemistry of Crossbred Sheep and Non-descript Goats of Jammu Region with Reference to Grazing and Browsing Adaptations - Sethi, Lovish; Sarma, Kamal; Suri, Shalini; Devi, Jonali; Sasan, Jasvinder Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study evaluated the histochemical distribution of major biochemical components in the tongue of crossbred sheep and non-descript goats across different age groups. Various lingual regions, including the tip, body, torus linguae, and root, were examined for neutral mucopolysaccharides, acidic mucopolysaccharides, glycogen, proteins, and lipids. Neutral mucopolysaccharides showed strong to intense PAS-positive reactions in the keratin layer of both species across all regions. The lamina epithelialis exhibited moderate PAS positivity, while the basement membrane showed strong reactions, comparatively more intense in goats. Most lingual tissues were negative for acidic mucopolysaccharides; however, lingual glands displayed strong Alcian Blue positivity, highlighting their role in mucin secretion and lubrication. Glycogen was absent in epithelial and connective tissue layers but was weak to moderately present in intrinsic muscle bundles and strongly expressed in lingual glands. Protein reactions were strong in the keratin layer and intrinsic muscles, while the lamina epithelialis showed age-related variation. Lipids were weak to moderate in the epithelium and basement membrane, moderate to strong in muscle bundles, and strong in lingual glands and blood vessels. Overall, both species exhibited similar histochemical distribution patterns, indicating comparable structural organization and functional adaptations of the tongue.